Chemical proteomics: a powerful tool for exploring protein lipidation - Storck,EM; Serwa,RA; Tate,EW (Biochemical Society Transactions, 2013)
The study of post-translational modifications such as protein lipidation is a non-trivial challenge of the post-genomic era. In recent years the field of chemical proteomics has greatly advanced our ability to identify and quantify protein lipidation. In the present review, we give a brief overview of the tools available to study protein acylation, prenylation and cholesterylation, and their application in the identification and quantification of protein lipidation in health and disease.